MENUMBUHKAN KREATIVITAS DAN PELESTARIAN LINGKUNGAN DI DESA HILIDOHONA KECAMATAN SIDUAORI - Sesilia S. Gee; Ade M.D.N.P; Alifn Buulolo; Ayusokho Baene; Berkat Waruwu; Candra B.D Laia; Mistarina Hulu; Sadarmin Indah Hulu; Sindi Hana Putri Zamili; Aluiwa’auri Tafona’o (Universitas Nias Raya, 2024)
Creativity plays an important role in improving the quality of life of the community, especially in villages with limited resources. This community service focuses on efforts to foster creativity and awareness of environmental conservation in Hilidohona Village through private tutoring programs and the production of environmentally friendly dishwashing soap. The private tutoring program is designed to improve the cognitive and social skills of children and adolescents in the village, with an emphasis on creative problem solving. Meanwhile, the initiative to make environmentally friendly dishwashing soap aims to reduce the use of hazardous chemicals that can pollute the environment, as well as provide economic value to the community. The collaboration between these two programs is expected to create a more innovative mindset while supporting the sustainability of the family economy and the environment in Hilidohona Village, Siduaori District. Initial results show an increase in environmental awareness and creative thinking skills among participants, which has the potential to bring long-term positive changes to Hilidohona Village.